A hybrid energy storage system with optimized operating strategy for mitigating wind power fluctuations. (September 2018) - Zhang, Yi; Xu, Yujie; Guo, Huan; Zhang, Xinjing; Guo, Cong; Chen, Haisheng
Abstract: A novel method based on hybrid energy storage system (HESS), composed of adiabatic compressed air energy storage (A-CAES) and flywheel energy storage system (FESS), to mitigate wind power fluctuations and augment wind power penetration is proposed in this paper. Wind power fluctuates in different frequencies, mainly divided into low and high frequency, which can be coped with by A-CAES and FESS respectively. To fit with low frequency fluctuation exhibiting large magnitude, A-CAES with multi-operating strategies is first proposed to widen operational ranges. Mathematical model of key components' off-design performance is established. For a 49.5 MW wind farm in China, design and optimization of HESS are comprehensively investigated. More specifically, the selection of A-CAES system's key components, such as compressor and expander, and parameters of them are specified as well as the parameters of FESS. The key operating parameters of the HESS, when integrated with wind plant, are analyzed and the characteristics are revealed. The results indicate that by HESS, wind power with fluctuation within 0–49.5 MW (average 25.55 MW) can be stabilized to a steady electrical power output of 24.18 MW. The loss of wind power is 6.6%, far less than the wind power rejection rate 17.1% in China. Highlights: A novel HESS is proposed for mitigating wind power fluctuations. Design and optimization methods of HESS are developed. An A-CAES system with wide operational range is first proposed. The rate of wind power connected to the grid increases to 93.4%.